A wind of change - Forrest, Bella (Forrest, Bella. Shade of vampire, 2015)
"From the ruins of the final battle, a new hero has emerged. A hero who will take The Shade into unchartered territories. Who will usher in a new world order, in which no predator may ever be safe again. And who will experience and learn to love, like no man has ever done before."--Page 4 of cover.